2013
DOI: 10.5120/10759-5699
|View full text |Cite
|
Sign up to set email alerts
|

Illumination Invariant Face Recognition

Abstract: Face Recognition is a term that includes several subproblems. Though face recognition have been a grown up research area, however, there still remain many problems that must be overcome to develop a robust face recognition system that works well under various circumstances such as illumination, pose and expressions variations. Such variations have proven to be one of the biggest problems of face recognition systems. In the proposed thesis work the problem of illumination is discussed. A method based on the com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 17 publications
(25 reference statements)
0
7
0
Order By: Relevance
“…The Quotient Image [5] uses the relative reflectance with respect to model images to represent a subject. Retinexbased approaches [6,7,11] aim to remove the illumination effect by estimating the illumination through filtering. Transformation-based methods [8][9][10][11] use phase or other…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…The Quotient Image [5] uses the relative reflectance with respect to model images to represent a subject. Retinexbased approaches [6,7,11] aim to remove the illumination effect by estimating the illumination through filtering. Transformation-based methods [8][9][10][11] use phase or other…”
Section: Related Workmentioning
confidence: 99%
“…For example, a variety of subspace-based methods have been proposed [3,4]. Methods based on illumination-invariant features have also been proposed [5][6][7][8][9][10][11][12][13][14]. On the other hand, previous studies have shown that spectral information is useful for this purpose [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%
“…We in work prevalent results on regular encounter requirements, along with a unique "in the wild" described dataset using the purpose of suggest our plan continue their stateof-the-art, from time to time somewhat [51]. In the prepared analysis work a technique on the basis of the group of Retinex and RECORD (DCT) plan is set up.…”
Section: Literature Review Of Associated Workmentioning
confidence: 99%
“…Author [8] employs the same engine feature space to reach the recognition in case of pose difference. Some other feature vectors applied by different researchers for improving the recognition accuracy in case of multiple feature difference parameters includes DCT, Nearest Neighbor Discriminant Analysis [10], LBP [12], Gabor Filter [13], textural feature [18] etc. These features are used individually or collectively for improving the recognition accuracy in case of head movement [14], pose variation [15], illumination [16][17] variant, age variation etc.…”
Section: Related Workmentioning
confidence: 99%